Pain relief in dysmenorrhea: Exploring hypnosis as an alternative therapy - Maitri Shah; Anuradha Monga; Sangita V Patel; Malay Shah; Harsh Bakshi (Wolters Kluwer Medknow Publications, 2016)
Objective: Dysmenorrhea is a widespread medical problem among young females. Hypnosis has been successfully tried for alleviation of different types of pain. In this randomized control trial, we compared it with nonsteroidal anti-inflammatory drug (NSAID), which is a standard treatment, for primary dysmenorrhea. Method: Out of 116 female nursing students, 50 having dysmenorrhea were selected and divided into mild, moderate, and severe pain category based on visual analog scale (VAS) score. Each category was randomly divided into two groups. One group was offered hypnosis and the other was offered Ibuprofen for pain relief in each menstrual cycle, for three consecutive cycles. They were followed for next three cycles (i.e., 4 th , 5 th , and 6 th cycle) without any treatment. Evaluation of pain score was done at the end of each cycle in both the groups. Wilcoxon Signed Rank Test and Mann-Whitney U-test were used for statistical analysis. Results: Compared to baseline, the improvement in pain scores was statistically significant in all six cycles in hypnosis group (P < 0.0001); whereas in NSAID group, the improvement was found during first three cycles only (P < 0.0001). Comparing the VAS scores of the same menstrual cycle in both the groups, it was less in NSAID group than hypnosis group for the first three cycles. This shows the instant effect of NSAID on pain relief. However, for the remaining cycles, pain scores were less in hypnosis group compared to NSAID group. Conclusion: For dysmenorrhea, hypnosis produces lasting pain relief compared to NSAID.